Evaluation on OmniSTAR wide area DGPS service - Subari, Mustafa Din; Che Awang, Mohamad Saupi; Supian, Hamsah; Suarni, Saiful Sukri (2004)
OmniSTAR is a wide Area Differential Global Positioning System (WADGPS). The system transmits differential GPS correction data world wide using a global network of reference stations (90 stations) to measure the errors induced into the GPS signal. This reference data is gathered at a network control center (NCC) (at Houston, Texas and Perth, Australia) where it is checked for integrity and reliability and it’s up-linked to a series of geo-stationary satellites, which distribute the data to the users worldwide. This paper describes project undertaken at the SNAG research Group at the Universiti Teknologi Malaysia. The study was conducted to specifically evaluate the performance of commercial WADGPS services that are assessable and available in Malaysia. OmniSTAR Performance Test has done for a of 28 days duration in May 2003 at UTM, Johor Bahru using Omnilite 132 DGPS Receiver. Initial results shows that while several days, service availability was 100%, there are days when service availability was only 90%. Horizontal accuracy was found to be consistently good to a meter while height accuracy was slightly worst.